Acceptability and Feasibility in a Pilot Randomized Clinical Trial of Computerized Working Memory Training and Parental Problem-Solving Training With Pediatric Brain Tumor Survivors. (15th March 2019) - Hocking, Matthew C; Paltin, Iris; Quast, Lauren F; Barakat, Lamia P
Abstract: Objective: To evaluate the feasibility and acceptability of computerized working memory training in pediatric brain tumor survivors (PBTS) with cognitive deficits, as well as computerized working memory training that is enhanced with parental problem-solving skills training (PSST). Methods: Twenty-seven PBTS (ages 7–16) recruited from a large, tertiary academic medical center were randomly assigned to computerized working memory training (Standard; n  = 14) or computerized working memory training plus PSST (Combined; n  = 13). PBTS completed a baseline assessment and parents completed acceptability surveys. Primary outcomes included number of intervention sessions completed and acceptability ratings. Results: Fourteen of the 27 participants completed at least 20 sessions of the computerized training with average sessions lasting over an hour ( M  =   68.42 min, SD = 14.63). Completers had significantly better baseline auditory attention abilities than noncompleters. Parents reported both frustration and satisfaction related to the interventions and identified barriers to completing intervention sessions. Conclusions: This pilot randomized clinical trial raises significant questions related to the feasibility of computerized working memory training in PBTS with cognitive deficits. Findings also offer considerations for integrating family-based treatment approaches into cognitive remediation interventions for PBTS.